Electromagnetic wave absorber and method for absorbing electromagnetic wave

JP2025034114APending Publication Date: 2025-03-13TOHOKU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023140295
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0008】 本発明の電磁波吸収体は、安価で大面積に製造でき、フレキシビリティを備えてあらゆる場所に設置が可能であり、かつ広帯域のテラヘルツ波の吸収体として用いることができる。 また本発明の電磁波吸収方法によれば、本発明の電磁波吸収体を用いることにより、テラヘルツ波を効率的に吸収させることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034114000001_ABST
    Figure 2025034114000001_ABST
Patent Text Reader

Abstract

To provide an electromagnetic wave absorber that is inexpensive, can be made large in area, can be installed in any place with flexibility, and can cope with a wide band of frequencies.SOLUTION: In an electromagnetic wave absorber 1 for absorbing a terahertz wave having a three-dimensional mesh structure of conductive fiber, each of a fiber body (a three-dimensional mesh structure of non-conductive fiber) 2 and a conductive substance 3 formed by sputtering forms an independent layer. The conductive substance 3 has a conductivity gradient such that an amount (a proportion) of the conductive substance 3 decreases in a depth direction of the fiber body 2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electromagnetic wave absorber and an electromagnetic wave absorbing method for absorbing terahertz waves using the electromagnetic wave absorber. [Background technology]

[0002] Anticipating the arrival of a data-driven "ultra-smart society" in the 2030s, a promotion strategy is underway to realize "Beyond 5G." Taking into account the expected volume of data communication and the number of communication devices in the 2030s, the goal of "Beyond 5G" is to achieve communication speeds 10 times faster than 5G in the access network and 100 times faster than current speeds in the core network. To achieve this goal, development is underway to efficiently and effectively utilize communication technologies that use terahertz waves, which are higher frequency electromagnetic waves.

[0003] Electromagnetic wave absorbers are used to prevent deterioration of reception level due to multiple interference of electromagnetic waves and deterioration of signal read rate due to noise. Currently, in order to prevent noise due to 5G microwaves (3 to 30 GHz), electromagnetic wave absorbers using magnetic materials with excellent electromagnetic wave absorption properties as fillers are used. For example, Patent Document 1 discloses a noise absorbing sheet in which at least two layers are laminated, in which a magnetic material layer containing a magnetic material and a layer of a noise absorbing fabric having metal attached to the constituent fibers are laminated, and the common logarithm value of the surface resistivity of at least one side of the noise absorbing fabric is in the range of 0 to 6. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2015 / 076387 Summary of the Invention [Problem to be solved by the invention]

[0005] With the use of high-frequency electromagnetic waves such as terahertz waves in communication technology, there is an urgent need to develop new materials that can efficiently absorb high-frequency electromagnetic waves (with excellent electromagnetic wave absorption properties). One of the reasons for this is that magnetic materials, which have excellent electromagnetic wave absorption properties for microwaves such as those used in conventional 5G, do not exhibit electromagnetic wave absorption properties for high-frequency electromagnetic waves such as terahertz waves. Therefore, expectations are high for electromagnetic wave absorbers that use metamaterials, an artificial optical material, as a new electromagnetic wave absorber that can also handle terahertz waves. On the other hand, metamaterials are usually manufactured using semiconductor microfabrication technology, which means that they are expensive, difficult to manufacture in large areas, and limited to flat substrates, making them inflexible and restricting their shape and processing. Furthermore, resonant metamaterials only support a narrow range of electromagnetic wave frequencies.

[0006] An object of the present invention is to provide an electromagnetic wave absorber that is inexpensive, can be made large, has flexibility so that it can be installed anywhere, and is compatible with a wide range of frequencies, and an electromagnetic wave absorption method for absorbing terahertz waves using the electromagnetic wave absorber. [Means for solving the problem]

[0007] The above-mentioned object of the present invention has been achieved by the following means. [1] An electromagnetic wave absorber for absorbing terahertz waves, having a three-dimensional mesh structure of conductive fibers. [2] The electromagnetic wave absorber according to [1] above, wherein the frequency of the terahertz waves is within a range of 0.1 to 10 THz. [3] The three-dimensional mesh structure of the conductive fiber has a void ratio of 40 to 99.9% and a basis weight of 10 to 3000 g / m 2 The electromagnetic wave absorber according to the above [1] or [2], [4] The electromagnetic wave absorber according to any one of [1] to [3], wherein the three-dimensional mesh structure of the conductive fibers is a nonwoven fabric structure. [5] The electromagnetic wave absorber according to any one of [1] to [4] above, wherein the three-dimensional mesh structure of the conductive fibers is such that at least a portion of the non-conductive fibers of the three-dimensional mesh structure is coated with a conductive substance. [6] The electromagnetic wave absorber according to [5] above, wherein the coating is a coating by a sputtering method. [7] The electromagnetic wave absorber according to [5] or [6] above, wherein the conductive material contains at least one metal selected from gold, silver, copper, aluminum, iron, nickel, chromium, titanium, tungsten, stainless steel, indium, tin, and zinc. [8] The electromagnetic wave absorber according to [5] or [6], wherein the conductive material includes a conductive metal oxide. [9] A method for absorbing an electromagnetic wave, comprising absorbing a terahertz wave by using the electromagnetic wave absorber according to any one of the above [1] to [8].

[10] An article for absorbing electromagnetic waves, comprising the electromagnetic wave absorber according to any one of [1] to [8] above. Effect of the Invention

[0008] The electromagnetic wave absorber of the present invention can be manufactured inexpensively and in a large area, has the flexibility to be installed anywhere, and can be used as an absorber for a wide band of terahertz waves. Furthermore, according to the electromagnetic wave absorption method of the present invention, the terahertz wave can be efficiently absorbed by using the electromagnetic wave absorber of the present invention. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is an example of a diagram showing a schematic cross section of each electromagnetic wave absorber of the present invention used in the examples. [Diagram 2] FIG. 2 is a graph showing an example of the measurement results of the terahertz wave absorption rate of each electromagnetic wave absorber in which an aluminum film is formed on the surface of a BEMCOT. [Diagram 3]FIG. 3 is a graph showing an example of the measurement results of the terahertz wave absorption rate of each electromagnetic wave absorber in which an aluminum film is formed on the surface of a BEMCOT. [Figure 4] FIG. 4 is a graph showing an example of the measurement results of the terahertz wave absorption rate of each electromagnetic wave absorber in which an aluminum film is formed on the surface of a BEMCOT. [Diagram 5] FIG. 5 is a graph showing an example of the measurement results of the reflectance of terahertz waves of each electromagnetic wave absorber in which an aluminum film is formed on the surface of a BEMCOT. [Figure 6] FIG. 6 is a graph showing an example of the measurement results of the terahertz wave absorption rate of each electromagnetic wave absorber in which a gold film is formed on the surface of BEMCOT. [Figure 7] FIG. 7 is a graph showing an example of the measurement results of the terahertz wave absorption rate of each electromagnetic wave absorber in which an aluminum film is formed on the surface of paper. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] A preferred embodiment of the present invention will be described below, but the present invention is not limited to the following embodiment except as specified by the present invention.

[0011] [Electromagnetic wave absorber] The electromagnetic wave absorber of the present invention has a three-dimensional network structure of conductive fibers. The electromagnetic wave absorber of the present invention is an electromagnetic wave absorber for absorbing terahertz waves. In the present invention and this specification, the term "terahertz waves" refers to electromagnetic waves having a frequency in the range of 0.1 to 10 THz. In the electromagnetic wave absorber of the present invention, the frequency of the terahertz waves is preferably in the range of 0.1 to 5 THz, more preferably in the range of 0.1 to 4 THz, even more preferably in the range of 0.1 to 3 THz, even more preferably in the range of 0.2 to 3 THz, and even more preferably in the range of 0.3 to 3 THz. In addition, in the present invention and this specification, a "three-dimensional mesh structure of conductive fibers" means that at least a portion of the fibers that make up the three-dimensional mesh structure are conductive fibers, or that the three-dimensional mesh structure is a mixed composite (homogeneous mixture, heterogeneous mixture, layered mixture) in which a three-dimensional mesh structure is formed by combining non-conductive fibers that make up the three-dimensional mesh structure and conductive fibers that make up the three-dimensional mesh structure.

[0012] The electromagnetic wave absorber of the present invention can have an absorptivity (electromagnetic wave absorptivity) of 70% or more, 80% or more, or even 90% or more for electromagnetic waves having a frequency in the range of 0.1 to 10 THz (preferably 0.1 to 5 THz, more preferably 0.1 to 4 THz, even more preferably 0.1 to 3 THz, even more preferably 0.2 to 3 THz, and even more preferably 0.3 to 3 THz). For example, in the examples (FIGS. 2 to 4 and 6) described later, it is shown that when the electromagnetic wave absorber of the present invention is irradiated with electromagnetic waves having a frequency in the range of 0.3 to 3.0 THz, the absorptivity (electromagnetic wave absorptivity) of the electromagnetic waves is 70% or more in all cases. In addition, the reflectivity (electromagnetic wave reflectivity) for electromagnetic waves in the frequency range can be 30% or less, 20% or less, or 10% or less. For example, in Example 5 described later, it is shown that when the electromagnetic wave absorber of the present invention was irradiated with the above-mentioned electromagnetic waves, the reflectance of the electromagnetic waves (electromagnetic wave reflectance) was 10% or less in all cases. The "reflectance" of the electromagnetic wave absorber can be determined by irradiating the electromagnetic wave absorber of the present invention with electromagnetic waves having each frequency in increments of 0.01 THz for the above frequency range, measuring the reflectance at the frequency, and calculating the arithmetic average of each measured value for the above frequency range. The "absorption" of the electromagnetic wave absorber can be determined by irradiating the electromagnetic wave absorber of the present invention with electromagnetic waves having each frequency in increments of 0.01 THz for the above frequency range, measuring the transmittance (electromagnetic wave transmittance) and reflectance at the frequency, calculating the absorbance at the frequency by the following (Formula 1), and determining the arithmetic average of each calculated value for the above frequency range. Absorption rate (%) = 100 - {Transmittance (%) + Reflectance (%)} (Equation 1)

[0013] The components of the electromagnetic wave absorber of the present invention are described below.

[0014] <Three-dimensional mesh structure of conductive fibers> In the present invention and this specification, the term "three-dimensional fiber network structure" means an assembly in which fibers are entangled three-dimensionally. For example, it means an assembly in which fibers are entangled three-dimensionally, such as the "three-dimensional fiber network structure" of a "nonwoven fabric" that is normally available on the market. On the other hand, the term "three-dimensional fiber network structure" means, as described above, that at least a part of the fibers constituting the three-dimensional network structure are conductive fibers, or that the three-dimensional network structure is formed by combining non-conductive fibers constituting the three-dimensional network structure with conductive fibers constituting the three-dimensional network structure to form a mixed composite (homogeneous mixture or heterogeneous mixture). The aforementioned "fibers at least a part of which are conductive" may be, for example, a structure in which a part or all of the fiber surface constituting the nonwoven fabric is covered with a conductive material. In addition, examples of nonwoven fabrics that are preferably used in the present invention include nonwoven fabrics made of long fibers and / or short fibers. It is preferable that all of these fibers have a certain degree of softness and a certain degree of strength. From the viewpoint of mass production and low cost, nonwoven fabrics containing long fibers are more preferably applied. The fiber diameter (equivalent circle diameter of fiber cross section) of the fibers constituting the three-dimensional network structure is not particularly limited as long as the desired effect is achieved. For example, the three-dimensional network structure can be formed by combining fibers having a fiber diameter of 0.01 μm to 100 μm as necessary.

[0015] The three-dimensional mesh structure of the conductive fibers preferably has a wide range of spatial frequency components. The three-dimensional mesh structure of the conductive fibers has a wide range of spatial frequency components, so that it can absorb electromagnetic waves over a wider range. From the viewpoint of obtaining a three-dimensional mesh structure having a wider range of spatial frequency components, it is preferable that the three-dimensional mesh structure of the conductive fibers has, for example, a high-order fractal structure, a structure in which thin fibers branch out from thick fibers, and / or a structure in which fibers are randomly arranged.

[0016] The three-dimensional mesh structure of the conductive fibers preferably has a gradient of conductivity in the thickness direction (perpendicular to the installation surface of the electromagnetic wave absorber) as described below. In order to provide such a gradient, the three-dimensional mesh structure preferably has a small apparent density and an appropriate void ratio and basis weight. It is more preferable that the three-dimensional mesh structure of the conductive fibers is not compacted. The density of the three-dimensional mesh structure of the conductive fibers (apparent density (bulk density), synonymous with the apparent density of the electromagnetic wave absorber) is 0.01 to 1 g / cm 3 and preferably 0.02 to 0.5 g / cm 3 More preferably, the density is 0.03 to 0.3 g / cm 3 More preferably, the density is 0.05 to 0.2 g / cm 3 It is more preferable that the apparent density is 100% or more. Note that the apparent density can be calculated by dividing the mass of the electromagnetic wave absorber by the volume of the electromagnetic wave absorber (volume including voids). The porosity of the three-dimensional network structure of the conductive fibers (synonymous with the porosity of the electromagnetic wave absorber) is preferably 40 to 99.9%, more preferably 60 to 99.9%, even more preferably 80 to 97%, and even more preferably 90 to 97%. The porosity can be determined by the following formula 2. Porosity (%) = {1 - (apparent density of three-dimensional mesh structure of conductive fibers / true density of three-dimensional mesh structure of conductive fibers)} × 100 (Equation 2) In addition, the basis weight of the three-dimensional mesh structure of the conductive fiber (synonymous with the basis weight of the electromagnetic wave absorber) is 10 to 3000 g / m2 It is preferable that the thickness is 15 to 1000 g / m 2 More preferably, the thickness is 20 to 200 g / m 2 More preferably, the thickness is 25 to 100 g / m 2 It is even more preferable that: In addition, the basis weight of the three-dimensional mesh structure of non-conductive fibers in the "three-dimensional mesh structure of conductive fibers" made of fibers at least partially having conductivity is usually 1 to 1000 g / m 2 , preferably 10 to 100 g / m 2 , more preferably 10 to 30 g / m 2 A range of is used.

[0017] The thickness of the three-dimensional mesh structure of the conductive fiber is not particularly limited, and from the viewpoint of exhibiting higher electromagnetic wave absorption properties and further increasing the flexibility of the conductive fiber, it is preferably 0.1 to 10 mm, more preferably 0.5 to 5 mm, and even more preferably 1 to 3 mm.

[0018] The conductive fiber used in the present invention may be a fiber that constitutes the three-dimensional mesh structure of the conductive fiber itself composed of a known conductive polymer, or may be a fiber having a three-dimensional mesh structure of non-conductive fiber as a base material and a conductive material coated on the fiber. Since there is a tendency that the absorption rate of electromagnetic waves can be improved and the reflectance rate of electromagnetic waves can be reduced by providing a gradient of conductivity (high conductivity or low conductivity) in the thickness direction, the three-dimensional mesh structure of the conductive fiber is preferably a three-dimensional mesh structure of non-conductive fiber as a base material and coated with a conductive material from one side of the three-dimensional mesh structure using a sputtering method described later. The "coated" state means that at least a part of the fibers that constitute the three-dimensional mesh structure is coated.

[0019] As described above, the three-dimensional mesh structure of the conductive fiber preferably has a gradient of conductivity (high conductivity or low conductivity) in the thickness direction of the electromagnetic wave absorber. With a moderate gradient of conductivity, the electromagnetic wave that enters the three-dimensional mesh structure of the conductive fiber is captured by the conductive material and converted into an electric current, and when the conductivity decreases toward the inside (the surface opposite to the electromagnetic wave irradiation surface), the electrical resistance value increases toward the inside, and the electrical resistance makes it easier to convert the electrical energy into heat energy, so that the electromagnetic wave can be efficiently absorbed. In addition, by having a gradient of conductivity in the thickness direction, impedance is matched from the outside to the inside, and the reflection of the electromagnetic wave can be effectively suppressed. It is also preferable to provide a gradient of conductivity in the thickness direction of the electromagnetic wave absorber so that the conductivity increases toward the inside, and the advantages of this will be described later. The conductivity gradient can be formed, for example, by coating one side of the three-dimensional network structure with a conductive material by the method described below.

[0020] Examples of fibers that form a three-dimensional mesh structure include non-conductive fibers such as chemical fibers (synthetic fibers made from petroleum-based raw materials such as polyester, nylon, and acrylic, and regenerated fibers such as cellulose fibers made by refining natural wood, etc.) and natural fibers (plant fibers such as cotton and hemp, and animal fibers such as raw silk and wool). Examples of fibers that are inherently conductive include fibers containing elemental carbon, such as fibers made of carbon nanotubes and fibers made of graphite. When a fiber has at least a portion thereof being conductive, the fiber itself can be formed into a three-dimensional mesh structure. When a fiber does not have conductivity (is a non-conductive fiber), it can be coated with a conductive material as described above. Examples of the three-dimensional mesh structure include a nonwoven fabric structure, a cloth structure (woven fabric structure), a knit structure, and a paper structure (a mesh sheet structure of pulp fibers), and the like. A nonwoven fabric structure is preferred. Among these, a nonwoven fabric structure having voids of random shape and size is preferred. A nonwoven fabric structure in which the constituent fibers have a random branching structure is also preferred.

[0021] Examples of conductive substances include metals, conductive metal oxides, conductive polymer materials, and nanocarbon materials (eg, graphene, carbon nanotubes, etc.), and materials with large conductor loss are preferred. Examples of metals or conductive metal oxides include gold, silver, copper, aluminum, iron, nickel, chromium, titanium, tungsten, stainless steel, and the like, as well as oxides of the metals (e.g., conductive titanium oxide, tungsten oxide, etc.), and other conductive metal oxides (indium tin oxide (ITO), indium zinc oxide (IZO), etc.). That is, the conductive substance preferably contains at least one metal selected from gold, silver, copper, aluminum, iron, nickel, chromium, titanium, tungsten, stainless steel, indium, tin, and zinc. The metal may be in the form of a compound (oxide, etc.) so long as it is conductive. On the other hand, examples of the conductive polymer material include known conductive polymers. In the electromagnetic wave absorber of the present invention, one type of conductive substance may be used alone, or two or more types may be used in combination. Among them, from the viewpoint of raw material cost and process cost, the conductive substance preferably contains a conductive substance selected from aluminum, gold, and copper, and more preferably contains aluminum and / or gold.

[0022] Methods for imparting conductivity to non-conductive fibers or their three-dimensional mesh structures include coating the fibers (or fibrous bodies) with a conductive substance by sputtering deposition, EB (electron beam) deposition, plating, spray coating, thermal evaporation, chemical treatment, etc. When the three-dimensional mesh structure of non-conductive fibers is coated with a conductive substance by the above-mentioned method, for example, at least one surface of the three-dimensional mesh structure of non-conductive fibers can be coated with the conductive substance. It is also preferable to coat both surfaces of the three-dimensional mesh structure of non-conductive fibers with the conductive substance.

[0023] When a conductive material is coated on the three-dimensional mesh structure of non-conductive fibers, the amount of conductive material applied can be appropriately set according to the type of conductive material. For example, when the conductive material is aluminum, the amount of application is 1 cm 3D mesh structure of non-conductive fibers. 3 The amount of the conductive material is preferably 30 mg to 10 g, more preferably 45 mg to 3 g, and even more preferably 60 mg to 0.6 g per cm of the three-dimensional mesh structure of the non-conductive fiber. 3 Preferably, the weight is 210 mg to 75 g, more preferably 320 mg to 22 g, and even more preferably 430 mg to 4.4 g per unit area. For example, when forming an aluminum or gold film on the surface of a three-dimensional mesh structure of non-conductive fibers by sputtering, the amount of adhesion can be set within the above-mentioned preferred range by coating the aluminum or gold under the conditions described in the examples.

[0024] The electromagnetic wave absorber of the present invention may be, for example, an electromagnetic wave absorber consisting of one layer of a three-dimensional mesh structure of conductive fibers, or may be an electromagnetic wave absorber consisting of a laminate (two or more layers, more preferably three or more layers) of three-dimensional mesh structures independent of each other of conductive fibers. Examples of the electromagnetic wave absorber consisting of one layer of the above-mentioned three-dimensional mesh structure include FIG. 1(a) "one sheet front", FIG. 1(b) "one sheet back", FIG. 1(e) "two sheets front", and FIG. 1(g) "two sheets back". Examples of the above-mentioned laminate (two layers) include FIG. 1(c) "one sheet both", FIG. 1(d) "one sheet front, two layers", and FIG. 1(f) "one sheet back, two layers". By laminating the three-dimensional mesh structure of conductive fibers, the absorption rate of terahertz waves can be further improved (see FIG. 2 to FIG. 4). That is, in the electromagnetic wave absorbing method for absorbing terahertz waves using the electromagnetic wave absorber of the present invention, a method of laminating three-dimensional mesh structures independent of each other of conductive fibers is preferably applied. Furthermore, in the electromagnetic wave absorber of the present invention, when independent three-dimensional mesh structures of conductive fibers are laminated as described above, each of the laminated three-dimensional mesh structures may be made of a different material, but it is preferable that they are made of the same material (the same material and substantially the same structure).

[0025] Since the electromagnetic wave absorber of the present invention is used for absorbing terahertz waves, it may be in a form that does not contain a magnetic material (for example, a material with a relative magnetic permeability of more than 50, preferably a material with a relative magnetic permeability of more than 100, and more preferably a material with a relative magnetic permeability of more than 200). This is because, as the frequency increases, the relative magnetic permeability decreases and the impedance decreases, so that even if a magnetic material is contained, terahertz waves cannot be absorbed.

[0026] Since the electromagnetic wave absorber of the present invention is an aggregate of conductive fibers, it is lightweight, has excellent flexibility, and can be processed into various shapes. For example, if the three-dimensional mesh structure of the conductive fibers is a structure that can be folded like paper, it can be easily formed into a three-dimensional shape by folding the paper. For example, if it is formed into a pyramid or box shape, the surface area of ​​the electromagnetic wave absorber per unit area can be increased to improve the electromagnetic wave absorption characteristics, and if it is formed into a pyramid shape with a sub-wavelength period, the average conductivity gradient can be made to be greater in the depth direction, thereby improving the electromagnetic wave absorption characteristics. In addition, if it is folded into a bellows shape, the elasticity is improved, and the electromagnetic wave absorber can be installed in the elastic part. Furthermore, by controlling the pitch of the unevenness of the bellows, electromagnetic waves with a wavelength of the same length as the pitch can be selectively and strongly absorbed, and the wavelength selectivity and the selected wavelength can be tuned. In addition, if the three-dimensional mesh structure of the conductive fibers is a flexible structure like cloth (woven fabric, nonwoven fabric, etc.), it can be formed by cutting, sewing, etc., into a shape that wraps around the target object. Therefore, the electromagnetic wave absorber of the present invention can be used for various purposes. As a more specific example of the shape of an article, the electromagnetic wave absorber of the present invention may be in the form of a bag, such as clothing, an electromagnetic wave absorbing curtain, wallpaper, a fibrous heat insulating material, a tapestry, an electromagnetic wave absorber for an anechoic chamber, a drawstring bag, etc. Furthermore, by having the electromagnetic wave absorber of the present invention on (or overlapping) an article requiring electromagnetic wave absorption, such as clothing, an electromagnetic wave absorbing curtain, wallpaper, a fibrous heat insulating material, a tapestry, and a pyramidal electromagnetic wave absorber for an anechoic chamber, it is also possible to efficiently absorb electromagnetic waves in a wider band.

[0027] [Electromagnetic wave absorption method] Another embodiment of the present invention is a method for absorbing terahertz waves by using the electromagnetic wave absorber of the present invention. The preferred frequency range of the terahertz waves to be absorbed is as described in the electromagnetic wave absorber of the present invention. From the viewpoint of absorbing terahertz waves more efficiently by the electromagnetic wave absorber of the present invention, when the electromagnetic wave absorber of the present invention is one surface of a three-dimensional mesh structure coated with a conductive material, the surface coated with the conductive material can be used as the surface opposite to the surface irradiated with terahertz waves. Although the academic reason why terahertz waves can be efficiently absorbed in this way is not clear, it is presumed to be due to the following mechanism. Fresnel reflection increases due to a sudden change in impedance (refractive index). The impedance (refractive index) gradually changes in the depth direction at the interface between the air of the incident layer and the electromagnetic wave absorber, resulting in a non-reflective surface, and the electromagnetic wave incident on the electromagnetic wave absorber is absorbed and finally dissipated as thermal energy. Therefore, it is considered that reflection can be suppressed and the absorption rate can be increased by making the electromagnetic wave incident from the side of the conductive material with a lower density, which is opposite to the coating surface of the conductive material. EXAMPLES

[0028] The present invention will be described in more detail with reference to the following examples. The present invention is not to be construed as being limited to the following examples except as defined in the present invention.

[0029] Example 1 <Preparation of electromagnetic wave absorber with three-dimensional mesh structure of conductive fibers> A nonwoven fabric, BEMCOT (registered trademark, model number: M-1, thickness: 0.26 mm, manufactured by Asahi Kasei Corporation), was cut into a length of 30 mm and a width of 30 mm, and if necessary, two sheets were stacked together to be used as a three-dimensional mesh structure of nonconductive fibers. The apparent density of BEMCOT used in the examples was 0.083 g / cm. 3 , porosity 94%, basis weight 27.5g / m 2 It was. An Al film was formed on one or both sides of the surface of the three-dimensional mesh structure of non-conductive fibers by a sputtering device (sputtering deposition). The sputtering conditions were voltage 400 V, argon gas (flow rate 60 to 70 sccm), and deposition time 30 minutes. In addition, when the measurement surface (the surface on which the electromagnetic wave is incident) is taken as the front surface, the electromagnetic wave absorber in which aluminum (conductive material) is sputtered from the front side is called "one sheet front" (Fig. 1(a)), the electromagnetic wave absorber in which a conductive material is sputtered from the back side is called "one sheet back" (Fig. 1(b)), the electromagnetic wave absorber in which a conductive material is sputtered from both the front and back sides is called "one sheet both" (Fig. 1(c)), and the electromagnetic wave absorber in which a conductive material is sputtered from the front side is called "one sheet front" (Fig. 1(d)). The electromagnetic wave absorber in which the BEMCOT is doubled and a conductive material is sputtered from the front side is called "one sheet, two layers" (Fig. 1(d)), the electromagnetic wave absorber in which the BEMCOT is doubled and a conductive material is sputtered from the front side is called "two sheets, front" (Fig. 1(e)), the electromagnetic wave absorber in which the BEMCOT is doubled and a conductive material is sputtered from the back side is called "one sheet, two layers, back" (Fig. 1(f)), and the electromagnetic wave absorber in which the BEMCOT is doubled and a conductive material is sputtered from the back side is called "two sheets, back" (Fig. 1(g)). In addition, in each electromagnetic wave absorber 1 shown in Fig. 1, the fibrous body (three-dimensional mesh structure of non-conductive fibers) 2 and the conductive material 3 are shown to form independent layers, but in this embodiment, the conductive material 3 has a conductivity gradient formed so that the amount (proportion) of the conductive material 3 decreases in the depth direction of the fibrous body 2 (downward in Fig. 1(a)).

[0030] <Method for measuring electromagnetic wave absorption rate and electromagnetic wave reflectance> For each of the electromagnetic wave absorbers produced as described above, the electromagnetic wave absorptivity and electromagnetic wave reflectivity when irradiated with terahertz waves in the range of 0.3 to 3.0 THz were measured by the following method. The electromagnetic transmittance of the obtained electromagnetic wave absorbers was measured by a terahertz spectrometer (TeraProspector, manufactured by Nippou Precision Co., Ltd.). A continuous holder (aperture diameter 10 mm) was used as the sample holder. The electromagnetic reflectance of the electromagnetic wave absorbers was measured by attaching a unit of the reflection automatic sample stage UNT (TP-RFL-1) for terahertz spectrometer to the terahertz spectrometer. From the transmittance and reflectance measured as above, the electromagnetic wave absorptance of the terahertz waves was calculated according to the following formula (1). Absorption rate (%) = 100 - {Transmittance (%) + Reflectance (%)} (Equation 1) In addition, BEMCOT that was not sputtered was used as a control, and the electromagnetic wave absorption rate was measured in the same manner as above. The results of the electromagnetic wave absorption rate measured by the above method are shown in Figures 2 to 4, and the results of the electromagnetic wave reflectance are shown in Figure 5.

[0031] As is clear from Figures 2 to 4, each electromagnetic wave absorber in which aluminum is sputtered onto BEMCOT exhibits an extremely high electromagnetic wave absorption rate of approximately 90% or more for electromagnetic waves in the frequency range of 0.3 to 3.0 THz. In addition, it was revealed that the electromagnetic wave absorption characteristics were higher when electromagnetic waves were irradiated from the side opposite the side on which the aluminum was sputtered (back of one sheet) than when electromagnetic waves were irradiated from the side on which the aluminum was sputtered (front of one sheet), and further that the electromagnetic wave absorption characteristics were higher when aluminum was sputtered on both sides (front and back) of a single BEMCOT sheet and electromagnetic waves were irradiated (both sheets) (Figure 2).

[0032] Furthermore, by comparing "1 sheet front" and "1 sheet front 2 layers" in Fig. 3 and "1 sheet back" and "1 sheet back 2 layers" in Fig. 4, it became clear that an electromagnetic wave absorber consisting of two layers of a three-dimensional mesh structure of conductive fibers has superior electromagnetic wave absorption properties compared to one consisting of a single layer of a three-dimensional mesh structure of conductive fibers. Also, by comparing "1 sheet front" and "2 sheets front" in Fig. 3 and "1 sheet back" and "2 sheets back" in Fig. 4, it was shown that thicker BEMCOT tends to have superior electromagnetic wave absorption properties. It should be noted that the BEMCOT itself used as a control had an absorption rate of less than 80% for electromagnetic waves in any of the above frequency ranges.

[0033] As is clear from FIG. 5, the reflectance of each of the electromagnetic wave absorbers (one sheet, front, one sheet (front and back)) was kept low in the range of 0.3 to 3.0 THz.

[0034] Example 2 Each electromagnetic wave absorber was obtained by sputtering a film on the front or back surface of the BEMCOT in the same manner as in Example 1 above, except that a gold film was sputtered instead of aluminum. For each of the obtained electromagnetic wave absorbers, the electromagnetic wave absorptivity was measured when irradiated with terahertz waves in the range of 0.3 to 3.0 THz in the same manner as in Example 1. The results are shown in FIG.

[0035] As is clear from Figure 6, each electromagnetic wave absorber (one sheet front, one sheet back) in which gold was sputtered onto BEMCOT showed high absorption rates for electromagnetic waves in the frequency range of 0.3 to 3.0 THz. It was also revealed that the electromagnetic wave absorption characteristics were higher when electromagnetic waves were irradiated from the side opposite to the side on which gold was not sputtered (one sheet back) than when electromagnetic waves were irradiated from the side on which gold was sputtered (one sheet front). It should be noted that the BEMCOT itself used as a control had an absorption rate of less than 60% for electromagnetic waves in any of the above frequency ranges.

[0036] Example 3 Instead of BEMCOT, paper (Multipaper Super White+, thickness: 0.09 mm, manufactured by Askul Corporation) cut to a length of 25 mm and a width of 25 mm was used, and the same procedure as in Example 1 was used to obtain each electromagnetic wave absorber having an aluminum film formed by sputtering on one or both sides. The basis weight of the paper used was 68 g / m 2 The electromagnetic wave absorbency of each of the obtained electromagnetic wave absorbers was measured when irradiated with terahertz waves in the range of 0.3 to 3.0 THz in the same manner as in Example 1. The results are shown in FIG.

[0037] As is clear from FIG. 7, the electromagnetic wave absorber using paper as the fibrous body had excellent absorption characteristics for terahertz waves from the surface opposite to the surface on which the aluminum film was formed by sputtering (rear surface).

[0038] Example 4 Each electromagnetic wave absorber was obtained by sputtering a film on the front or back surface of the BEMCOT in the same manner as in Example 1 above, except that a film was formed by sputtering using iron instead of aluminum. The electromagnetic wave absorbency of each of the obtained electromagnetic wave absorbers was measured when irradiated with terahertz waves in the range of 0.3 to 3.0 THz in the same manner as in Example 1. As a result, it was shown that each of the electromagnetic wave absorbers had excellent terahertz wave absorption characteristics (figure omitted).

[0039] As described above, the electromagnetic wave absorber of the present invention can be produced inexpensively and in a large area, has flexibility and can be installed anywhere, and exhibits high characteristics as an absorber of a wide band of terahertz waves. In particular, the electromagnetic wave absorber of the present invention, which has a three-dimensional mesh structure of conductive fibers, has a highly reliable electromagnetic wave absorbing performance with flexibility by providing a conductive material to at least a part of the non-conductive nonwoven fabric or the like. [Explanation of symbols]

[0040] 1. Electromagnetic wave absorber 2. Fiber body (three-dimensional mesh structure of non-conductive fibers) 3 Conductive substances

Claims

1. An electromagnetic wave absorber for absorbing terahertz waves, having a three-dimensional mesh structure of conductive fibers.

2. 2. The electromagnetic wave absorber according to claim 1, wherein the frequency of the terahertz wave is within a range of 0.1 to 10 THz.

3. The three-dimensional mesh structure of the conductive fiber has a void ratio of 40 to 99.9% and a basis weight of 10 to 3000 g / m 2 3. The electromagnetic wave absorber according to claim 2,

4. The electromagnetic wave absorber according to claim 3 , wherein the three-dimensional mesh structure of the conductive fibers is a nonwoven fabric structure.

5. 5. The electromagnetic wave absorber according to claim 4, wherein the three-dimensional mesh structure of the conductive fibers is such that at least a portion of the non-conductive fibers of the three-dimensional mesh structure is coated with a conductive material.

6. 6. The electromagnetic wave absorber according to claim 5, wherein the coating is a coating formed by a sputtering method.

7. 7. The electromagnetic wave absorber according to claim 6, wherein the conductive material contains at least one metal selected from gold, silver, copper, aluminum, iron, nickel, chromium, titanium, tungsten, stainless steel, indium, tin, and zinc.

8. The electromagnetic wave absorber of claim 6 , wherein the conductive material comprises a conductive metal oxide.

9. A method for absorbing electromagnetic waves, comprising absorbing terahertz waves using the electromagnetic wave absorber according to any one of claims 1 to 8.

10. An article for absorbing electromagnetic waves, comprising the electromagnetic wave absorber according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Noise-absorbing sheet

    WO2015076387A1